Respostas de vertebrados terrestres de médio e grande porte a pressões antrópicas em três áreas protegidas na Amazônia Oriental - DE PAULA, Milton José (2020)
Medium-sized to large-bodied terrestrial vertebrates provide important environmental services in tropical forests, significantly contributing to the maintenance of these environments and often considered as keystone species. Local depletion these species can compromise the flow of these ecosystem functions inducing significant impacts on the trophic structure of the ecosystem. Hunting in tropical forests represents one of the most widespread threats to large-bodied vertebrates. However, game species contribute with an important primary source of dietary protein and are irreplaceable for the rural poor, who enjoy limited access to markets. The Amazon hosts the highest diversity of terrestrial vertebrate species worldwide, retains 52% of all remaining tropical forests, and the Brazilian Amazon accounts for the largest stronghold for these species. As estimated ~23.5 million animals are hunted annually by the rural population of the Brazilian Amazon. Part of this population (traditional people) occupy sustainable-use Protected Areas (PA) under the federal domain, which aims to conserve biodiversity under the premise of sustainable resource use. Even though hunting represents an important source of meat for local communities, their right to subsistence hunting is uncertain and often stigmatized. Moreover, there have been growing discussions about the degree to which hunting depletes large vertebrates in these PAs. In the first session of this thesis, I assessed the management and conservation potential of medium and large-sized terrestrial vertebrates species hunted by traditional peoples (ribeirinhos) of the Rio Iriri and Riozinho do Anfrísio Extractives Reserves (ER). Results indicated that hunting does not represent a meaningful demographic threat for these species, and that these two ER have great potential for the management and conservation of exploited game species. In the second session, I assessed the responses of medium and large-sized terrestrial mammal and bird species to anthropogenic pressure of ribeirinhos at the ER Rio Iriri and Terra do Meio Ecological Station (EE). The results showed that the areas used by ribeirinhos retain the entire complement of vertebrate species, and indicated that the relative abundances of these species did not respond to local anthropogenic disturbance, and this held true even for the most hunted species, Tayassu pecari. In the third session, I explored data from a camera-trapping study at the EE Terra do Meio. The results showed that agoutis (Dayprocta leporina) were most frequently recorded, and there was no statistically significant decline in the occupancy of the 25 medium and large-bodied terrestrial bird and mammal species examined here. Much of the apparent sustainability in game resource use is attributed to vast tracks of relatively intact forest within the mosaic of PA and the traditional way of life of ribeirinhos. Results in this doctoral dissertation reaffirm the importance of the large PAs for the conservation and sustainable management of medium and large-bodied vertebrates across the Amazon.